Effect of remineralization after in office followed by home treatment of white spot lesions in children randomized controlled trial - Maryam M. El Mansy; Mohamed F. Rashed; Reham S. Saleh (Scientific Reports)
Abstract To compare the effect of Nanohydroxy apatite (NHA), Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), CPP-ACP with fluoride (CPP-ACPF), versus fluoride gel on remineralization and color improvement of white spot lesions (WSLs) after clinical application followed by home treatment. Thirty-two children from 10 to 14 years with 100 teeth were participated in this study. Affected teeth were randomly allocated into five groups (n = 20); group I: NHA, group II: CPP-ACP, group III: CPP-ACP + F, group: IV: Fluoride gel and group V: no treatment. After application for five minutes, remineralization was assessed via diagnodent while Vita easy shade was used for color assessment before and after treatment. In- office procedures were repeated after one week and one month, while continuous home application was followed. Remineralization and color assessment were repeated at each interval. The remineralization ability and color change showed a significant difference between the examined groups at different intervals with p value < 0.001. Where group I had the significantly highest remineralization ability at different periods. While the color difference was significant in group III followed by group I after immediate application. However, at one-month group III had the most significant color change in all groups. NHA could be a potent remineralizing agent while improving the color of WSLs. CPP-ACP + F had a superior masking and sustainable effect of the WSLs. Combined in office followed by continuous home application of different remineralizing agents could mask the WSLs which satisfy the patients’ needs. Trial registration: This study was initially registered on https://ClinicalTrials.gov on 12/02/2025 as first posted date, with ID: NCT06821724 - https://clinicaltrials.gov/study/NCT06821724 .